ISLAM DAN OTORITAS KEAGAMAAN - Rumadi Rumadi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2012)
Is religion possible to grow without any authority? Generally people responded the question with two speculative answers: “religion can be and grow without any authority” and “religion can not be and grow without any authority”. The first opinion is based on the argumentation that religion constitutes a divine total comprehension. It does not need any other than the submission of human being to God. Meanwhile, the second opinion is based on the argumentation that religion constitutes individual rights to communicate and submit to God, but in social sphere the development of religion needs “distributors” having credibility to speak and transmit religious messages. However, in fact, religious authority is not a static one, but dynamic. Levels of religious authority and inter relation between the authority levels is a part of the dynamics.